Aspetti di sicurezza nell’utilizzo dei sistemi di navigazione satellitare - Leonardi, Mauro (GEOmedia, 2019)
Satellite navigation systems are more and more used in geomatics. This penetration has not always taken into account the relative safety and security aspects and the consequent threats to humans. This work focuses on these aspects that are often overlooked in geomatics. After a brief introduction on the evolution of satellite navigation systems and on future trends, the related safety and security risks are analyzed and possible countermeasures (Integrity, Awareness and Protection) are discussed.